The effect of candida albicans inoculation under acrylic and chrome- cobalt palatal plates (comparative study) - Mustafa Al-Ahmad, Basma Ezzat; Kashmola, Muhanad Ali Hamdon; Mustafa, Nazih Shaban; Abdullah, Nasuruddin (2014)
Denture stomatitis is common disease among maxillary denture wearers. Sixty Wistar rats were involved in this study devided into 2 experiment group in addition to 1 control group each contain 20 rats, group 1A include 10 animals fitted with acrylic and inoculated with candida albicans , group 1 B 10 animals were fitted with acrylic only , while in group 2 A 10 were fitted with chrome-cobalt palatal plates and inoculated with candida albicans, group 2 B 10 animals were fitted with chrome-cobalt only , and the control group is devided into 2 groups 10 animals were inoculated with candida albicans , and the other 10 where left without treatment . Palatal candidiasis resulted after one week of starting the experiment in group 1A. while at the second week, there was alternating epithelial hyperplasia and atrophy, intra-epithelial polymorphonuclear leukocyte infiltration and chronic inflammatory cell infiltration in the underlying connective tissue; hyphal invasion was not observed. In group 1A transmission of candida from yeast into mycelium started at the first week and mycelium predominated at the second week. Group 2A did not exhibit palatal candidosis, the transformation from blastospore to mycelium was limited. The only histological observation seen in the palatal mucosa of animals was slight hyper orthokeratinization at the fourth week, Histological study of the palate tissue shoes an increase in inflammatory cell infiltration throughout the time course of the infection. Palatal biofilm formation was commensurate with development of palatal erythema, which suggests a role for biofilm in the inflammatory response.